2010
DOI: 10.1002/anie.201005775
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Free Platinum‐on‐Gold Nanodendrites with Enhanced Catalytic Performance for Oxygen Reduction

Abstract: Inner value: A new high‐concentration synthesis of Pt nanodendrite employs Au‐seed‐mediated growth inside a hollow silica nanosphere (see picture). The resulting material is substantially more active than commercial Pt black in the oxygen reduction reaction. Pt nanodendrite colloid with tunable dispersity as well as hybrid nanocrystals of various metals were also fabricated by the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 35 publications
(24 reference statements)
0
73
0
Order By: Relevance
“…In contrast, the high-quality Pd/rGO composites with wellmonodispersity can be obtained in the presence of a surfactant. However, the removal of the surfactant under harsh conditions may lead to the decrease in catalytic performance because of the deformation of the nanoparticles [30]. Therefore, the simple and surfactant-free synthesis of the Pd/rGO composites is still a quite challenging issue.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the high-quality Pd/rGO composites with wellmonodispersity can be obtained in the presence of a surfactant. However, the removal of the surfactant under harsh conditions may lead to the decrease in catalytic performance because of the deformation of the nanoparticles [30]. Therefore, the simple and surfactant-free synthesis of the Pd/rGO composites is still a quite challenging issue.…”
Section: Introductionmentioning
confidence: 99%
“…Since Xia and co-workers confirmed that the Pd-Pt bimetallic nanodendrites were two and a half times more active on the basis of equivalent Pt mass for the oxygen reduction reaction (ORR) than the state-of-the-art Pt/C catalyst and five times more active than the first-generation supportless Pt-black catalyst [3], Pt-based bimetallic heteronanostructures have attracted considerable interest because these materials are urgently desired in proton-exchange membrane fuel cells (PEMFCs) [60][61][62]. Heterogeneous seeded growth is probably the most powerful route to construct bimetallic heterostructures [63][64][65][66][67][68].…”
Section: Heterostructurementioning
confidence: 95%
“…The Pd-Pt nanodendrites consisting of a dense array of Pt branches on a Pd nanocrystal core were synthesized in an aqueous solution by reducing K 2 PtCl 4 with L-ascorbic acid in the presence of 9-nm truncated octahedral Pd seeds, with the addition of PVP as a stabilizer [62]. The ligand-free Pt-on-Au nanodendrites could be obtained when an aliquot of Na 2 PtCl 4 was added to an aqueous suspension containing Au@h-SiO 2 nanospheres as seeds and L-ascorbic acid as the reducing agent [60]. Considering that the two-step synthetic methods based on seed-mediated growth are strongly dependent on the use of pre-formed faceted metal seeds to direct the subsequent growth of the Pt branches, Yamauchi and coworkers developed a very simple and high-yield route for the direct synthesis of Pt-on-Pd nanodendrites in aqueous solution without the need for any pre-formed Pd seeds [61].…”
Section: Heterostructurementioning
confidence: 99%
“…This type of metal/graphene heterostructure possessed a high electrochemical active area and thus exhibited much higher electrocatalytic activity towards methanol oxidation reaction than the conventional catalysts of platinum black and commercial E-TEK Pt/C. Yeo et al [ 82 ] prepared another type of Pt nanodendrites attained by Au seed-mediated growth inside hollow silica nanoshells and demonstrated that such Pt nanocatalysts had substantially higher activity than commercial Pt black in the ORR process. There are also many other reports on the synthesis of highly branched nanostructures.…”
Section: Dendritic Nanostructures For Catalysismentioning
confidence: 99%